HLA‐DRB1*03:49, a novel allele identified by group‐specific sequence‐based typing in a north European individual. Issue 5 (16th October 2013) - Wallis‐Jones, S.; McWhinnie, A. J.; Madrigal, J. A.; Latham, K.; Marsh, S. G. E.
<x xml:space="preserve">Abstract</x> Identification of the antigen presenting molecule HLA‐DRB1*03:49 by group‐specific sequence‐based typing.